Weaving with the mind: The chumbe inga from the colombian Alto Putumayo as mental and cultural artifact - Aldana Barahona, Giovanna María; Sánchez Carballo, Alfredo (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2021)
This article presents the findings of an investigation about the sash named chumbe, made by the inga weavers of the Santiago-Manoy town of the upper Putumayo in Colombia. The objective of this work is to elucidate and comprehend the characteristics of the inga chumbe as cultural and mental artifact, in so far as it condenses and it’s a place of inscription of the significance nets of the inga people culture. The methodology used is qualitative. The tools applicated at the field work were semi-structured interview, the participant observation and a photographical register of the chumbe and the pictograms it contains. One of the main conclusions is that the Chumbe Inga, as a mental and cultural artifact, is an ‘art of memory’ in which the Inga people express their worldview and their ancestral technical and aesthetic knowledge.